SbWRKY75- and SbWRKY41-mediated jasmonic acid signaling regulates baicalin biosynthesis - Fang, Shiyuan; Zhang, Chen; Qiu, Shi; Xiao, Ying; Chen, Kaixian; Lv, Zongyou; Chen, Wansheng (Frontiers in Plant Science, 2023)
Introduction Scutellaria baicalensis Georgi is a traditional Chinese medicinal plant with broad pharmacological activities whose main active ingredient is the flavonoid baicalin. Given its medicinal value and increasing market demand, it is essential to improve the plant’s baicalin content. Flavonoid biosynthesis is regulated by several phytohormones, primarily jasmonic acid (JA). Methods In this study, we conducted transcriptome deep sequencing analysis of S. baicalensis roots treated with methyl jasmonate for different durations (1, 3, or 7 hours). Leveraging weighted gene co-expression network analysis and transcriptome data, we identified candidate transcription factor genes involved in the regulation of baicalin biosynthesis. To validate the regulatory interactions, we performed functional assays such as yeast one-hybrid, electrophoretic mobility shift, and dual-luciferase assays. Results Our findings demonstrated that SbWRKY75 directly regulates the expression of the flavonoid biosynthetic gene SbCLL-7, whereas SbWRKY41 directly regulates the expression of two other flavonoid biosynthetic genes, SbF6H and SbUGT, thus regulating baicalin biosynthesis. We also obtained transgenic S.baicalensis plants by somatic embryo induction and determined that overexpressing SbWRKY75 increased baicalin content by 14%, while RNAi reduced it by 22%. Notably, SbWRKY41 indirectly regulated baicalin biosynthesis by modulating the expression of SbMYC2.1, SbJAZ3 and SbWRKY75. Discussion This study provides valuable insights into the molecular mechanisms underlying JA-mediated baicalin biosynthesis in S. baicalensis. Our results highlight the specific roles of transcription factors, namely SbWRKY75 and SbWRKY41, in the regulation of key biosynthetic genes. Understanding these regulatory mechanisms holds significant potential for developing targeted strategies to enhance baicalin content in S. baicalensis through genetic interventions.